2014
DOI: 10.1007/s12079-014-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

New considerations on hormetic response against oxidative stress

Abstract: In order to survive living organisms have developed multiple mechanisms to deal with tough environmental conditions. Hormesis is defined as a process in which exposure to a low dose of a chemical agent or environmental factor that is damaging at higher doses induces an adaptive beneficial effect on the cell or organism. In this paper, we examine several ideas that might be taken into consideration before using hormesis as a therapeutic tool to improve health and life span, and hopefully will open the discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 95 publications
(184 reference statements)
1
28
0
Order By: Relevance
“…Oxidative hormesis is defined as a process in which exposure to a low dose of an oxidant induces an adaptive antioxidant protective response [34]. While SIH is usually classified as a preventive antioxidant, our results suggest that SIH iron chelators can also display antioxidant effects via an oxidative hormesis effect mediated by Nrf2 activation.…”
Section: Discussionmentioning
confidence: 64%
“…Oxidative hormesis is defined as a process in which exposure to a low dose of an oxidant induces an adaptive antioxidant protective response [34]. While SIH is usually classified as a preventive antioxidant, our results suggest that SIH iron chelators can also display antioxidant effects via an oxidative hormesis effect mediated by Nrf2 activation.…”
Section: Discussionmentioning
confidence: 64%
“…EDCs are capable of mediating changes in methylation patterns and regulate epigenetic encoding in cells, and epigenetic program control by such compounds are now well documented [6770]. Oxidative stresses are now also considered [31, 71]. A number of genes, viz.…”
Section: Endocrine Disrupting Chemicals (Pcbs Exposures) and Developmmentioning
confidence: 99%
“…For example, it has been shown that reactive oxygen species activate the nuclear transcription factor erythroid-derived 2-like 2 (Nrf2), which induces the expression of various antioxidant enzymes, and provide cells effective neutralization and clearance mechanisms of these radicals (Dodson et al, 2015;Jimenez-Osorio et al, 2015;Luna-Lopez et al, 2014;Ma and He, 2012a;Schieber and Chandel, 2014;Wang and Hai, 2011). We have recently shown that α,β-unsaturated reactive 4-hydroxyalkenals also evoke hormetic responses in vascular endothelial cells and pancreatic beta cells exposed to increasing levels of glucose and palmitic acid (Cohen et al, 2011Riahi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%